The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1001/archderm.134.9.1081
|View full text |Cite
|
Sign up to set email alerts
|

Disease Associations in Polymorphous Light Eruption

Abstract: To examine the long-term outcome of polymorphous light eruption (PLE) in a large patient population and to evaluate associated conditions, especially lupus erythematosus, during the course of the disease.Design: A questionnaire-based follow-up study an average of 32 years after onset of PLE. The study was complemented by clinical examination of the patients with PLE similarly studied 16 years earlier or now reporting equal or worse PLE symptoms compared with the 1978-1979 followup or any symptoms suggesting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 28 publications
4
20
0
1
Order By: Relevance
“…There was hypothyroidism in 11 out of 94 (11.7%) female cases in the study of Hasan et al . [5] They reported that PLE is a long-standing, slowly ameliorating disease with some tendency to development of autoimmune disease or thyroid disorder, especially in female patients. Seetharam and Sridevi found 27 female cases (31.3%) and 3 female controls out of 112 cases and 40 controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was hypothyroidism in 11 out of 94 (11.7%) female cases in the study of Hasan et al . [5] They reported that PLE is a long-standing, slowly ameliorating disease with some tendency to development of autoimmune disease or thyroid disorder, especially in female patients. Seetharam and Sridevi found 27 female cases (31.3%) and 3 female controls out of 112 cases and 40 controls.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Thyroid function abnormalities have been found to occur in patients with sunlight-associated dermatoses such as melasma and PLE. [345] Therefore, a comparative study of thyroid function tests (TFTs) was carried out among 100 cases of PLE with equal number of controls. The clinicoepidemiological features of PLE were also noted to find its relation with TFT.…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphous light eruption is a frequent UV-induced dermatitis of papular, papulovesicular, or plaquelike appearance. 36,56 The skin manifestations are monomorphous in the individual patient, and the disease is most common from March through June in geographic areas with a temperate climate, but can appear at any time of the year in tourists traveling to sunny areas. Young women are most often affected, and there is no restriction to race or age.…”
Section: Commentmentioning
confidence: 99%
“…Similarly Kochupillai 8 suggested a significant relation between PMLE and thyroid disease rather than a mere coincidence. Hasan et al 5 ., stated that PMLE is a long standing, slowly ameliorating disease with some tendency to development of autoimmune disease or thyroid disorder, especially in female patients.…”
Section: Discussionmentioning
confidence: 98%
“…Thyroid function abnormalities have found to occur in patients with sunlight associated dermatosis such as melasma and PLE [3][4][5] . Therefore, a comparative study of thyroid function tests would be carried out among minimum No.…”
Section: Introductionmentioning
confidence: 99%